The Impact of Spotify Music Platform on Students’ English Pronunciation: A Pre-Experimental Study - Nur Fitra; Abd. Kamaruddin; Hastini Hastini; Zarkiani Hasyim (MASI Mandiri Edukasi, 2025)
This study examines the impact of the Spotify music platform on improving the English pronunciation of eighth-grade students at MTs Muhammadiyah Al-Haq Palu, with a specific focus on the articulation of liquid consonants (/l/ and /r/), which commonly present difficulties for Indonesian learners of English. A quantitative pre-experimental design, utilising a one-group pre-test and post-test model, was employed with a sample of 28 students. Pronunciation tests were administered before and after the treatment to evaluate progress. The results revealed a significant improvement, as indicated by the increase in the mean score from 9.36 to 15.25, supported by a t-value of 27.36, which exceeds the t-table value of 2.052. These findings demonstrate that English songs on Spotify offer repetitive and authentic listening input, which strengthens articulation accuracy. The novelty of this study lies in analysing differential improvement between /l/ and /r/ sounds through a Spotify-based intervention. The implication suggests that digital music platforms can be used as effective supplementary tools in pronunciation teaching.